High-stakes interviews and rapport development: practitioners’ perceptions of interpreter impact - Goodman-Delahunty, Jane (Policing and society, 2019)
In high-stakes interviews on matters of national and international security, interpreters are essential when interviewers and interviewees lack a common language. Although rapport-based interviews are effective in eliciting more complete and accurate information from witnesses and suspects in monolingual interviews, little is known about an interpreter’s influence on rapport in interpreter-assisted interviews. Experienced interviewers (N = 121) drawn from policing, intelligence and military organisations in Australia, Indonesia, the Philippines, Sri Lanka and South Korea participated in structured interviews about interpreter-assisted interviews with high-value targets. Interview transcripts were coded for categorical information and analysed thematically. The reported challenges included concerns arising from poor adherence to professional ethics for interpreters and difficulty in establishing rapport with interviewees. Practitioners discussed the ways in which they responded to these challenges. Advance briefing of interpreters to better prepare them for the interview and adherence to sound interview practices were generally seen as beneficial. Implications of the findings for rapport-based interviews are discussed in terms of professional codes of ethics and conduct for interpreters. Aspects of policy, practice and research are identified for further attention to foster effective high-stakes interpreter-assisted interviews.